The impact of sugar‐sweetened beverage taxes on purchases: Evidence from four city‐level taxes in the United States. (28th July 2020) - Cawley, John; Frisvold, David; Jones, David
Abstract: Since 2017, many US cities have implemented taxes on sugar‐sweetened beverages to decrease consumption of sugary beverages and raise revenue. We analyze household receipt data to examine the impact of taxes on households' beverage purchases in the four largest US cities with such taxes: Philadelphia, PA; San Francisco, CA; Seattle, WA; and Oakland, CA. We compare changes in monthly household purchases in the treatment cities with changes in two comparison groups: (1) areas adjacent to the treatment cities or (2) a matched set of households nationally. An increase in the tax rate of 1 cent per ounce decreases household purchases of taxed beverages by 53.0 ounces per month (12.2%). This impact is consistent with a reduction in individual consumption of 5 calories per day per household member and eventual reduction in weight of 0.5 pounds. However, the decline was concentrated in Philadelphia, where the tax decreased purchases by 27.7%. There was no change in purchases of taxed beverages in the other three cities combined.